Stages of maturity and removal of physical sarcotesta on seedling emergence and development of papaya - de Melo, Aniela Pilar Campos; Seleguini, Alexsander (Comunicata Scientiae, 2013)
The use of quality seedlings is important to the successful implementation of the cultivation of papaya. However, the presence of sarcotesta in seed dormancy and post-harvest fruit can harm the seedling production on a commercial scale. This way, in-house vegetation, was evaluated in the emergence and development of papaya seedlings the effects of combination of fruit ripening stage and physical methods of removing the sarcotesta. Adopted the completely randomized design, in factorial 2 x 4, with two stages of maturation (3 or 5) and four methods of extraction of the sarcotesta (witness, pressure on sieve under running water, friction in coarse sand or smear with thick plastic bristle brush). The maturation stage 3 was the most suitable for the extraction of seeds for the production of seedlings. The presence of the sarcotesta negatively affected the percentage and the emergency speed index, and root growth.  The pressure in sieve under running water, rubbing with coarse sand and smear brush with plastic bristles are suitable methods for removal of sarcotesta of papaya seeds.